Impact of leverage and managerial skills on shareholders' return - Tunde, Matemilola Bolaji; Amin Noordin, Bany Ariffin; Wan Ngah, Wan Azman Saini (Elsevier, 2013)
The recent financial crisis that saw an increase in the risk premium and shareholders’ return around the world is partly caused by the management use of excessive leverage. This paper investigates the effect of leverage and managerial skills on shareholders’ return. Our regression analysis that accounts for managerial skill factors reveals that leverage has a positive relationship with shareholders’ return. Similarly, managerial skills have a positive relationship with shareholders’ return. Based on the findings, the study suggests that leverage and managerial skills may be priced in equity valuation. We develop an index measure of managerial skills and use the upper-echelon theory of the management literature to explain how managerial skills relate to shareholders’ return.